Dynamics of Flourishing Buddhist Organization Culture: A Case Study on PATRIA Organization - Yanti, Bonita Eka Dama; Abdullah, Sri Muliati (LifeSciFi, 2025)
A strong organizational culture is vital for youth organizations to thrive, especially those rooted in religious values, yet diverse member backgrounds can create challenges. This study aims to identify factors shaping the organizational culture and explore its development dynamics. Using a qualitative case study approach, data were collected from October to December 2023 through observations, interviews, and documentation. Six participants, selected based on their active involvement and knowledge of the organization’s activities, provided insights into its culture. The findings reveal that motivation, participation, discipline, communication, support, achievement, satisfaction, and leadership drive the organization’s flourishing culture. These factors, influenced by Theravada Buddhist values like compassion and mindfulness, foster unity and commitment among members. Events such as Dhammacamp and Vesak celebrations highlight the organization’s success in promoting Buddhist teachings and youth development. In conclusion, the study shows that a culture grounded in Buddhist principles creates a positive environment, offering insights for other youth organizations. However, the small sample size and regional focus suggest further research to explore broader contexts.